Heat transport of nanofluid flow through a porous channel with thermal radiation effects. (November 2022) - Waqas, Hassan; Fida, Muzamil; Liu, Dong; Manzoor, Umair; Alghamdi, Metib; Muhammad, Taseer
Abstract: This research demonstrates the numerical investigation of mass and heat transport in a viscous magnetohydrodynamic nanofluid ( Au / H 2 O ) flow via channel with porous wall in the existence of metallized nanoparticles. Gold nanoparticles are frequently employed as preferred materials in a range of sectors due to their unique optical and physical features, such as surface plasmon oscillation for labelling, sensors, and photographing. Significant progress in biomedical domains has recently been made, with increased biocompatibility in medicines and disease treatment. Similarity modifications based on the boundary layer concept are utilized to transform controlling differential equations into a dimensionless set of ordinary differential equations. The bvp4c method with MATLAB software is used to analyze the ordinary differential equations. The governing variables influences are discussed. We found that when the compression of the walls is paired with the help of suction and under the conditions of modest outcomes of Reynolds number and contraction /relaxation variable, the movement of the flow is favored immediate to the boundary layer position on the wall. When wall respite is combined with the help of injections, however, the flow contiguous to the permeable wall diminishes. The findings of the investigation could be useful in bioengineering applications. The consequences of fluid variables on velocity gradient, concentration gradient, and temperature gradient are explored and graphically illustrated. The rates of velocity profile, mass and heat transfer at the boundary are computed and examined numerically.